Evaluation of IP-10 in Quantiferon-Plus as biomarker for the diagnosis of latent tuberculosis infection - Petrone, Linda; Vanini, Valentina; Chiacchio, Teresa; Petruccioli, Elisa; Cuzzi, Gilda; Schininà, Vincenzo; Palmieri, Fabrizio; Ippolito, Giuseppe; Goletti, Delia (Tuberculosis (Edinburgh, Scotland), 2018)
The QuantiFERON-TB Gold Plus (QFT-Plus) is a new test for latent tuberculosis infection (LTBI) diagnosis, in which has been added a new tube containing shorter peptides stimulating CD8 T-cells and CD4-stimulating-peptides. Measurement of alternative biomarkers to Interferon-γ (IFN-γ) in QFT-Plus may improve its sensitivity. Interferon-γ inducible protein 10 (IP-10), has been proposed as a tuberculosis (TB) biomarker. We aimed to evaluate the IP-10 accuracy in QFT-Plus for LTBI diagnosis. QFT-Plus was performed in 36 active TB, 31 LTBI and 16 healthy donors (HD). IP-10 was detected by ELISA. IP-10 is increased in TB1 and TB2 tubes in subjects with active TB and LTBI compared to HD. A ROC analysis comparing active TB and HD was performed and a cut-off of 1174 pg/mL for TB1 and 928.8 pg/mL for TB2 identified active TB with 86% sensitivity (Se) and 94% specificity (Sp). Moreover, increased IP-10 in response to TB1 was found in subjects with LTBI compared to those with active TB. A cut-off point of ≥16,108 pg/mL was chosen to maximize the test performance. However, the test predicted LTBI only with 58% Se and 61% Sp. These results suggest that IP-10 is an alternative biomarker to IFN-γ in the QFT-Plus format.